Urodynamics in patients with spinal cord injury: A clinical review and best practice paper by a working group of The International Continence Society Urodynamics Committee. Issue 2 (1st August 2017) - Schurch, Brigitte; Iacovelli, Valerio; Averbeck, Marcio A.; Carda, Stefano; Altaweel, Waleed; Finazzi Agrò, Enrico
Abstract : Aims: Urodynamics have been recommended and utilized in the evaluation of spinal cord injury (SCI) patients for many years, but there is no consensus on the optimal use and follow‐up strategy for these patients. In the present manuscript, after reporting the available evidence, a working group of the Urodynamics Committee of the International Continence Society (ICS) provides the current knowledge and recommendations on patients' assessment, indications, role, technical aspects, and follow‐up of urodynamic studies in SCI patients. Methods: The working group has analyzed the current available evidence‐based literature leading to a Delphi consensus formation by the members of the working group. A set of questions derived from the search were answered online on several occasions by an international panel of specialists. A 1‐day face‐to‐face meeting of the experts finalized the discussion. Recommendations and expert opinions were finally reviewed by all the members of the ICS Urodynamics Committee on SCI core panel. Results: Six experts participated in the four phases of the consensus process. Evidence was reviewed. There was substantial variability in the level and quality of detail reported across the literature yield. Several papers reported insufficient detail to allow synthesis of outcomes across studies. The findings of this preliminary review have been used to generate guidelines for best practice of urodynamics in SCI patients. The working group included recommendations for patients' pre‐testing and urodynamic tests execution. Best practices were given as expert opinions where evidence was lacking. Conclusion: Urodynamic is highly recommended for patients with SCI after a proper initial assessment. Regular urodynamic follow‐up is recommended to avoid upper urinary tract damage. However, until now, there is limited evidence on how frequently urodynamic control should be performed.